Context specificity of the EMT transcriptional response - Cook, David P.; Vanderhyden, Barbara C. (Nature communications, 2020)
Epithelial–mesenchymal plasticity contributes to many biological processes, including tumor progression. Various epithelial–mesenchymal transition (EMT) responses have been reported and no common, EMT-defining gene expression program has been identified. Here, we have performed a comparative analysis of the EMT response, leveraging highly multiplexed single-cell RNA sequencing (scRNA-seq) to measure expression profiles of 103,999 cells from 960 samples, comprising 12 EMT time course experiments and independent kinase inhibitor screens for each. We demonstrate that the EMT is vastly context specific, with an average of only 22% of response genes being shared between any two conditions, and over half of all response genes were restricted to 1–2 time course experiments. Further, kinase inhibitor screens revealed signaling dependencies and modularity of these responses. These findings suggest that the EMT is not simply a single, linear process, but is highly variable and modular, warranting quantitative frameworks for understanding nuances of the transition. It is unclear if a common EMT expression program exists. Here, the authors perform multiplexed single-cell RNA sequencing across 12 EMT time courses and 16 kinase inhibitor screens, and find that EMT transcriptional responses are context specific and EMT is not a single, linear transition.